Peri-Ictal Changes in Depression and Anxiety in Persons With Epileptic and Non-epileptic Seizures - Hopp, Jennifer; Pahlavan, Autusa; Richert, Mary; Grimes, Kathryn; Turlington, Kate; Cassady, Maureen; Kvarta, Mark D.; Thompson, Scott M. (Frontiers in Psychiatry, 2022)
Objective We tested the hypothesis that epileptic, but not non-epileptic, seizures would produce an improvement in comorbid depression and anxiety symptoms in the peri-ictal period, much like the antidepressant effects of electroconvulsive therapy. Methods We examined depression and anxiety symptoms in patients admitted to an inpatient unit for continuous video electroencephalography as part of routine clinical care. Patients completed three questionnaires that included the Beck Depression Inventory-II (BDI), Montgomery Asberg Depression Rating Scale (MADRS), and Beck Anxiety Inventory (BAI) after admission, in the 24 h following a seizure, then again 2 weeks after the last seizure. Results In patients with epilepsy, depression and anxiety scores improved in the 24 hrs following a seizure (change in BDI = 24%; change in MADRS = 19%; change in BAI = 21%) but returned toward baseline after 2 weeks. In patients with non-epileptic seizures, depression and anxiety scores also improved in the 24 hrs following a psychogenic non-epileptic seizure (change in BDI = 17%, change in MADRS = 27%, change in BAI = 36%). There was a greater improvement in depression and anxiety scores in patients with focal-onset epilepsy (BDI = 30%, MADRS = 22%, BAI = 30%) compared to generalized seizure onset (BDI = 6%, MADRS = 12%, BAI = 8%). Conclusion We conclude that single seizures can result in transient improvements in mood. Because seizures need not be generalized or epileptic to exert this effect, the underlying mechanisms are uncertain.